2001
DOI: 10.1002/humu.10017
|View full text |Cite
|
Sign up to set email alerts
|

Ten novelFBN2mutations in congenital contractural arachnodactyly: Delineation of the molecular pathogenesis and clinical phenotype

Abstract: Congenital contractural arachnodactyly (CCA) is an autosomal dominant condition that shares skeletal features with Marfan syndrome (MFS), but does not have the ocular and cardiovascular complications that characterize MFS. CCA and MFS result from mutations in highly similar genes, FBN2 and FBN1, respectively. All the identified CCA mutations in FBN2 cluster in a limited region similar to where severe MFS mutations cluster in FBN1, specifically between exons 23 and 34. We screened exons 22 through 36 of FBN2 fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
96
0
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(103 citation statements)
references
References 22 publications
2
96
0
5
Order By: Relevance
“…Importantly, reports on four probands also mention aortic root dilatation, a feature previously thought to be a differentiating finding from Marfan syndrome (MFS; MIM] 154700) [Gupta et al, 2002[Gupta et al, , 2004.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Importantly, reports on four probands also mention aortic root dilatation, a feature previously thought to be a differentiating finding from Marfan syndrome (MFS; MIM] 154700) [Gupta et al, 2002[Gupta et al, , 2004.…”
Section: Introductionmentioning
confidence: 95%
“…However, only four groups explicitly stated that they had screened the entire FBN2 gene [Belleh et al, 2000;Maslen et al, 1997;Nishimura et al, 2007;Park et al, 1998], and CCA patients without FBN2 mutations were reported [Gupta et al, 2002]. Moreover, a premature truncating mutation was reported in CCA [Gupta et al, 2002] and could occur in other regions of the gene as well. It therefore remains unclear whether mutations outside the middle region of the FBN2 gene might cause CCA.…”
Section: Introductionmentioning
confidence: 98%
“…42,49 Similarly, patients with congenital contractural arachnodactyly or Beals syndrome due to mutations in FBN2 have had aortic root enlargement without documented progression to dissection. 50,51 There are other genetic syndromes that have multiple reports or documentation of thoracic aortic aneurysms leading to Type A dissections. There are multiple case reports of AoD in patients with autosomal dominant polycystic kidney disease.…”
Section: Class Iibmentioning
confidence: 99%
“…Mutations in fibrillin-1 result in Marfan syn-drome and some related disorders (33), whereas mutations in fibrillin-2 have been shown to lead to congenital contractural arachnodactyly (34,35). The "prototype" of microfibrillar disorders, Marfan syndrome, is primarily characterized by symptoms in the cardiovascular, skeletal, and ocular systems.…”
mentioning
confidence: 99%